Unveiling the Rarity: Primary Signet Ring Cell Carcinoma of the Prostate - Kaur, Navkiran; Dogra, Natasha; Shelly, Divya; Das, Amit Kumar; Pareek, Tarun (Annals of Pathology and Laboratory Medicine, 2025)
Primary prostatic signet-ring carcinoma is a rare and aggressive histological variant of adenocarcinoma, characterized by mucin-filled signet-ring cells. While this type of carcinoma can occur in various organs, including the stomach, colon, pancreas, breast, thyroid, bladder, and prostate, it is most commonly found in the stomach and colon. We present the case of an 88-year-old male patient who presented with hematuria. On digital rectal examination, prostatomegaly was noted. A finger-guided prostate biopsy was performed, and histopathological examination revealed primary prostatic signet- ring carcinoma. This diagnosis is one of exclusion, as metastasis from other sites, such as the gastrointestinal or urogenital systems, must be ruled out. Comprehensive imaging and clinical assessment are essential to ensure the primary origin of the carcinoma. Given the rarity of the disease, there is no established treatment protocol for primary prostatic signet-ring carcinoma. However, aggressive multimodal treatment, including surgery, chemotherapy, and/or radiation, can be considered based on the individual case, extent of disease, and overall patient condition. Early detection and a tailored therapeutic approach may improve prognosis, but this remains a challenging condition to manage.